Genetic diversity of Bartonella spp. in vampire bats from Brazil - Andre, Marcos R. [UNESP]; Gutierrez, Ricardo; Ikeda, Priscila [UNESP]; Amaral, Renan Bressianini do [UNESP]; Marques de Sousa, Keyla Carstens; Nachum-Biala, Yaarit; Lima, Luciana; Teixeira, Marta M. G.; Machado, Rosangela Z. [UNESP]; Harrus, Shimon (Wiley-Blackwell, 2019)
Recently, an increasing number of Bartonella species have been emerged to cause human diseases. Among animal reservoirs for Bartonella spp., bats stand out due to their high mobility, wide distribution, social behaviour and long-life span. Although studies on the role of vampire bats in the epidemiology of rabies have been extensively investigated in Latin America, information on the circulation and genetic diversity of Bartonella species in these bat species is scarce. In the present work, 208 vampire bats, namely Desmodus rotundus (the common vampire bat; n = 167), Diphylla ecaudata (the hairy-legged vampire bat; n = 32) and Diaemus youngii (the white-winged vampire bat; n = 9) from 15 different states in Brazil were sampled. DNA was extracted from liver tissue samples and submitted to real-time PCR (qPCR) and conventional PCR (cPCR) assays for Bartonella spp. targeting five genetic loci, followed by phylogenetic and genotype network analyses. Fifty-one out of 208 liver samples (24.51%) were positive for Bartonella DNA in the ITS real-time PCR assay [40 (78.43%) of them were from D. rotundus from 11 states, and 11 (21.57%) samples from D. ecaudata from three states. Eleven genotypes were found for each gltA and rpoB genes. Several ITS sequences detected in the present study clustered within the lineage that includes B. bacilliformis and B. ancachensis. The Bayesian phylogenetic inference based on the gltA gene positioned the obtained sequences in six different clades, closely related to Bartonella genotypes previously detected in D. rotundus and associated ectoparasites sampled in Latin America. On the other hand, the Bartonella rpoB genotypes clustered together with the ruminant species, B. schoenbuchensis and B. chomelii. The present study describes for the first time the molecular detection of Bartonella spp. in D. ecaudata bats. It also indicates that Bartonella spp. of vampire bats are genetically diverse and geographically widespread in Brazil.
Keywords: bartonellosis; Desmodus rotundus; Diaemus youngii; Diphylla ecaudata; Latin America